Barriers to mental health treatment: results from the WHO World Mental Health surveys. Issue 6 (9th August 2013) - Andrade, L. H.; Alonso, J.; Mneimneh, Z.; Wells, J. E.; Al-Hamzawi, A.; Borges, G.; Bromet, E.; Bruffaerts, R.; de Girolamo, G.; de Graaf, R.; Florescu, S.; Gureje, O.; et al.
Abstract : Background: To examine barriers to initiation and continuation of mental health treatment among individuals with common mental disorders. Method: Data were from the World Health Organization (WHO) World Mental Health (WMH) surveys. Representative household samples were interviewed face to face in 24 countries. Reasons to initiate and continue treatment were examined in a subsample ( n = 636 78) and analyzed at different levels of clinical severity. Results: Among those with a DSM-IV disorder in the past 12 months, low perceived need was the most common reason for not initiating treatment and more common among moderate and mild than severe cases. Women and younger people with disorders were more likely to recognize a need for treatment. A desire to handle the problem on one's own was the most common barrier among respondents with a disorder who perceived a need for treatment (63.8%). Attitudinal barriers were much more important than structural barriers to both initiating and continuing treatment. However, attitudinal barriers dominated for mild-moderate cases and structural barriers for severe cases. Perceived ineffectiveness of treatment was the most commonly reported reason for treatment drop-out (39.3%), followed by negative experiences with treatment providers (26.9% of respondents with severe disorders). Conclusions: Low perceived need and attitudinal barriers are the major barriers to seeking and staying in treatment among individuals with common mental disorders worldwide. Apart from targeting structural barriers, mainly in countries with poor resources, increasing population mental health literacy is an important endeavor worldwide.